Effect of samarium and vanadium co-doping on structure, ferroelectric and photocatalytic properties of bismuth titanate. Issue 16 (2nd February 2017) - Ramana, E. Venkata; Prasad, N. V.; Tobaldi, David Maria; Zavašnik, Janez; Singh, M. K.; Hortigüela, María Jésus; Seabra, M. P.; Prasad, G.; Valente, M. A.
Abstract : A systematic analysis of the structure, ferroelectricity and photocatalytic activity (PCA) of Sm and V modified Bi4 Ti3 O12 was performed. Highly reproducible gas–solid phase PCA of NO x abatement and improved ferroelectricity were achieved. Abstract : We performed a systematic analysis of the structure, ferroelectric and photocatalytic activities of Sm and V co-doped Bi4 Ti3 O12 (SBVT) ceramics. The formation of 3-layered Aurivillius structure and chemically induced strain of SBVT were analyzed by SEM and HRTEM studies. From the results of structural refinements, temperature dependent XRD and Raman spectra we found that SBVT has a distorted orthorhombic structure and transforms to tetragonal in the temperature range of 475–600 °C. Raman modes of Bi sites experience the phase transition earlier compared to torsional bending modes of BO6 octahedra. From the results of polarization and piezoelectric strain measurements, we found that SBVT exhibits superior ferroelectric characteristics as well as improved S 33 (0.02 × 10 −3 ) compared to other rare-earth doped Bi4 Ti3 O12 materials reported in the literature. SBVT exhibited fatigue endurance up to 10 8 switching cycles. Such a behavior is attributed to the structural distortions due to the smaller ionic radius of Sm 3+ and reduced oxygen vacancies. Local piezoresponse measurements demonstrated imprint characteristics of ferroelectric domains. Furthermore, we assessed the photocatalytic (PC) activity of SBVT – for the first time – in the gas–solid phase, monitoring the degradation of nitrogen oxides ( i.e. NO + NO2 ). Results demonstrated that SBVT was photocatalytically active in the solar spectrum, being able to degrade NO x at ppb level concentration, and exhibited a very stable PC activity (five consecutive PC runs), proving itself suitable for reuse.